SISTEM INFORMASI AKUNTANSI DALAM MENINGKATKAN PENGENDALIAN INTERNAL ATAS PENDAPATAN RUMAH SAKIT UMUM MURHUM KOTA BAUBAU - Salihi, Said Saleh; Wiansari, Wiansari (Pusat Studi Ekonomi, Publikasi Ilmiah dan Pengembangan SDM, 2022)
Analyze the accounting information system in improving internal control over revenue at the Murhum General Hospital, Baubau City.The type of data used in this study is qualitative data. The data collection techniques used in this study are observation, interviews and documentation. Data analysis techniques using qualitative descriptive are analyzing, describing, summarizing various conditions and situations collected in the form of the results of interviews or observations regarding the problems studied that occur in the field.The results of this study accounting information system in improving internal control over revenue at the Murhum general Hospitals, Baubau City it is not adequate even though it plays a role in increasing internal control over hospital revenues.There is a clear division of functions between operational functions, reception and storage functions and recording and reporting functionsinternal control of revenue carried out by Murhum General Hospital has not been effective and efficient in accordance with the elements of the internal control system except for risk assessment and monitoring that still needs attention.